Control of Neonectria ditissima with copper based products in New Zealand - Walter, M.; Stevenson, O.D.; Amponsah, N.T.; Scheper, R.W.A.; Rainham, D.G.; Hornblow, C.G.; Kerer, U.; Dryden, G.H.; Latter, I.; Butler, R.C. (New Zealand Plant Protection, 2015)
New Zealand pipfruit crops require postharvest fungicides for control of European canker caused by Neonectria ditissima Fungicide efficacy trials to protect leaf scars from N ditissima infections were conducted during autumn 2013 and 2014 Disease control of artificially inoculated leaf scars was achieved by single applications of copper oxychloride and copper oxide but not copper hydroxide applied at 43 11 and 06 kg elemental copper/ ha respectively Control of leaf scar infections by copper oxide (065 and 095 kg elemental copper/ha) was similar to control by captan Leaf scars (010 days old) remained susceptible to infections up to 10 days after leaf fall; disease control was achieved by redistribution of copper and captan fungicides onto new leaf scars Disease control using copper oxide was consistent and similar to control using captan The copper product and concentration of elemental copper are important for successful control of leaf scar infections by N ditissima